The Influence of Self-Efficacy, Family Environment, And the Role of The Teacher on Interest in Continuing Education to Higher Education - Wardani, Sukma Dwi Indah; Rahmaningtyas, Wisudani (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2023)
The purpose of this research is to determine the simultaneous and partial influence of self-efficacy, family environment, and the role of teachers on interest in continuing their education to higher education among students majoring in Office Management and Business Services at SMK Negeri 1 Kendal. The type of research used is quantitative research methods. The population in this study were Office Management and Business Services students for the 2022/2023 academic year at SMK Negeri 1 Kendal, totaling 213 students with a sample of 139 students. The sampling technique uses proportional random sampling. Data collection methods were carried out by means of questionnaires, interviews and documentation. The data analysis technique uses descriptive percentage analysis and multiple linear regression analysis. The results shows that there is an influence of self-efficacy, family environment, and the role of teachers on students' interest in continuing their education to higher education, both simultaneously and partially.